Energy absorption analysis of a novel foam-filled corrugated composite tube under axial and oblique loadings. (August 2018) - Mahbod, Mahshid; Asgari, Masoud
Abstract: Composite thin-walled structures are of much interest in differnet applications as well as energy absorption devices for their great crashworthiness and light weight. In this paper, a new corrugated composite cylindrical tube has been introduced in order to improve crashworthiness along with a stable crushing. In cylindrical composite tubes, the effects of corrugations regarding charactristics of energy absorption have underwent quasi-static axial and oblique loading investigations. For this reason, composite cylindrical tubes with different corrugation geometries were analyzed using finite element explicit code and the effects of corrugations on crush force effiency and specific energy absorption were comperhensively studied. The finite element model has been validated by experimental quasi-static compression tests. An efficient analytical solution for SEA during axial loading has been also derived and compared with FEM solution. Furthermore, a comparison of empty and foam-filled corrugated composite tubes has been done. Based on the obtained results, generating corrugated surfaces on tubes improved the crush force efficiency significantly in both axial and oblique crushings. Performing a parametric study on geometrical corrugation parameters of tubes has been indicated that the energy absorption of these structures depends strongly on the corrugation parameters. Furthermore the absorbed energy has been increased by using foams in both axial and oblique crushing. SEA increases by increasing the foam density while the CFE decreases. Highlights: An efficient theoretical formulation developed for composite corrugated foam-filled tubes under axial loading. Comprehensive numerical investigation considering crashworthiness behavior under oblique and axial crushing. The effect of geometrical parameters in corrugated composite tubes on energy absorption.